Process Development and Scale-Up of a Novel Atypical DAT Inhibitor (S)-CE-123 - Perez Gonzalez, Eduardo R. [UNESP]; Reck, Bernhard; Kalaba, Predrag; Langer, Thierry; Leban, Johann; Lubec, Gert (American Chemical Society (ACS), 2023)
Large-scale syntheses of small molecules and kilo laboratories are crucial steps in drug development, especially in advanced stages. (S)-5-((Benzhydrylsulfinyl)methyl)thiazole, (S)-CE-123, a potent, selective, and novel atypical DAT inhibitor, has undergone iterative testing as part of the preclinical evaluation step. This required the process transfer, scale-up, and synthesis of a 1 kg preclinical batch. The Kagan protocol for asymmetric sulfide to sulfoxide oxidation was successfully applied within a four-step synthetic process for the successful upscaling of (S)-CE-123. During the scale-up of the last step, several changes were made to the original synthetic procedure, as with every increase in batch size, new problems had to be overcome. These include, among others, the workup optimization of the last step, the simplification of chromatographic purification, elution modification to improve the purity of the product and saving of workup time. Two washing steps were added to the original procedure to enhance both the yield and the enantiomeric excess value of the final product. The modifications introduced allowed access to a 1 kg (S)-CE-123 batch with a purity >99% and an enantiomeric excess value of 95%.